PENGARUH ELECTRONIC WORD OF MOUTH TERHADAP KEPUTUSAN PEMBELIAN TIKET PESAWAT PENGGUNA MELALUI PLATFORM DIGITAL AIRASIA SUPERAPP - Budiarto, Dinda Adellia; Sasrawan Mananda, IGPB.; Sudana, I Putu (Jurnal IPTA (Industri Perjalanan Wisata); Vol 11 No 1 (2023): Jurnal IPTA (July 2023), 2023)
Airasia superapp is an application released by Airasia in the transformation from an airline company to a digital lifestyle company, however, many reviews about their service are found on social media. This study aims to analyze about the forms of electronic word of mouth (E-WOM), the user’s behavior, and the effect of E-WOM on airline ticket purchase decisions of users through airasia superapp. This study was using samples of 70 respondents that ever experienced in buying an airline ticket through airasia superapp which determined by purposive sampling method and data analysis in this study uses descriptive quantitative with a simple linear regression analysis. The results of this study indicated that forms of E-WOM influence as positive reviews discussing the promotions and negative reviews discussing on how the application works. In general, the users had fewer interactions with other users on social media and the process of purchase decisions with planned travel, information evaluations comparison and there is a significant effect of E-WOM on airline ticket purchasing decisions through airasia superapp.